Prevalence and factors associated with trichomonas vaginalis among women aged 15-49 years old attending the gynecology out patient department, Vientiane, Lao PDR - Douangphachanh, Keophouvanh (2001)
This cross-sectional study was conduted among 382 women aged 15-49 years old who attended the outpatient gynecological clinic in Mahosot and Setthatirath Hospitals in Vientiane, Lao PDR. It aimed to i.) estimated the prevalence and identify the factors associated with trichomonas vaginalis; ii.) compare the prevalence of STD signs and symptoms among cases and non-cases of trichomonas vaginalis; and iii.) determine health seeking behavior of women who are symptomatic for sexually transmitted diseases (STDs).Trichomonas vaginalis was detected in 12.6(95CI: 9.5to 16.4). The prevalence of muco-purulent vaginal discharge was significantly higher (p=0.044) among cases (8.3) compared to non-cases (2.7) of trichomonas vaginalis. Likewise, the prevalence of frothy vaginal discharge among cases and non-cases of trichomonas vaginalis was significantly higher (p=0.0001) among cases (27.1) compared to non-cases (4.5).The majority of women (81) went for consultation and treatment when they had signs and symptoms of STD. Of these, 91.0went to consult a doctor. The most common reason for not seeking consultation despite the presence of STD symptoms was the women's perceptin that these symptoms were to be considered a health problems (91.5). Approximately 12of symptomatoc women self-medicated.Multiple logistic regression was performed to quantify the relationship between various independent variables and trichomonas vaginalis controlling for the effect of age, education, abnormal vaginal discharge, vaginal pain/itching and vaginal odor.The results indicate that women whose families had lower monthly income (OR=2.9; 95CI: 1.3-6.7), those who had their sexual debut at a younger age (OR=1.8; 95CI: 0.9-3.7) and those whose spouses had other partners within the past twelve months (OR=2.3; 95CI: 1.2=4.5) were more likely to be infected with trichomonas vaginalis.Thus, the health education component of the intervention for the prevention and control of sexually transmitted diseases among women, particularly trichomonas vaginalis, should pay special attention to women in low-income groups.It should include messages concerning i.) the importance of delaying one's sexual debut, ii.) the need to seek consultation when one experiences STD signs and symptoms, particularly muco-purulent and frothy vaginal discharge; and iii.) the dangers of self-medicating.The results suggest that behavior change messages directed to women only, particularly if they are married, may not achieve its goal of preventing STDs. It should also target males to make them aware of the untoward consequences, not only to themselves but to their spouses as well, of having multiple partners.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Trichomonas vaginalis